Clonagem, expressão e purificação das enzimas NahE e NahK de Pseudomonas putida para determinação de suas estruturas cristalográficas - Samuel Leite Guimarães (2011)
Many pollutants are released to the environment due the use of petroleum and its derivatives. Some of them are classified as Polycyclic Aromatic Hydrocarbons (PAHs). Most of PAHs, or their metabolites, can interact with nitrogenous bases or cause lesions in DNA, potentiating mutations and consequently inducing the development of cancer. As a result of this, in the last decades, the concerns about contamination of soil and groundwater by PAHs have substantially increased. Various microorganisms have the capacity to use these hazardous molecules as carbon and energy source. The use of these microorganisms and/or their enzymes for the elimination of PAHs to the environment is a potential strategy for bioremediation. One of the most common and hazardous PAH is naphthalene, and because of the bacteria Pseudomonas putida ability to completely degrade it, it has been the focus of numerous studies. This work was focused in the study of two enzymes from P. putida involved in naphthalene degradation: NahE (a hydratase-aldolase) and NahK (a decarboxylase). The main objectives of this work were the amplification and cloning of nahE and nahK genes, expression and purification of NahE and NahK enzymes for biochemical and structural assays. The genes were initially cloned into the expression vector pET28a-TEV and expressed in Escherichia coli. The recombinant protein NahE was mainly detected in insoluble fraction and different trials were performed to obtain the protein in the soluble fraction, without success. Soluble NahE was obtained only when using denaturizing conditions of purification followed by a refolding protocol. On the other hand, NahK was detected in the soluble fraction and was purified by affinity and size-exclusion chromatographies. The purified proteins were submitted to Dynamic Light Scattering and Circular Dichroism experiments. Crystallization assays were also performed with NahK aiming crystal growth for elucidation of its three-dimensional structure by X-Ray Crystallography.